Broodstock development and controlled breeding of cobia Rachycentron canadum (Linnaeus 1766) from Indian seas - Gopakumar, G; Abdul Nazar, A K; Tamilmani, G; Sakthivel, M; Kalidas, C; Ramamoorthy, N; Palanichamy, S; Maharshi, V Ashok; Rao, K Srinivasa; Rao, G Syda (Indian Journal of Fisheries, 2012)
Cobia, Rachycentron canadum has emerged as one of the topmost finfish species for mariculture. In India, cobia broodstockwas developed and induced breeding was achieved for the first time at Mandapam Regional Centre of the Central MarineFisheries Research Institute (CMFRI). The broodstock was developed in sea cages of 6 m diameter and 3.5 m depth. Sexeswere separated about two months prior to the onset of breeding season and stocked in separate cages. During March 2010, afemale with intra-ovarian egg diameter of 700 Î¼ along with two males were selected for induced spawning. The brooderswere induced with human chorionic gonadotropin (hCG) at doses of 500 IU per kg body weight for female and 250 IU perkg body weight for males. Spawning was noted after 39 h of intra-muscular injection. The total eggs spawned wereestimated as 2.1 million. About 90% fertilization was recorded (fertilized eggs amounted to 1.9 million). The eggs werecollected using a 500 Î¼ mesh net and stocked in incubation tanks at varying densities. The eggs hatched after 22 h ofincubation at a temperature range of 28-30 ÂºC. The percentage of hatching was 80% and the total number of newly hatchedlarvae was estimated as 1.5 million.